Optimizing The Use of Big Data to Improve Guest Experience in International Hotels - Solikhah, Mar’atus (Politeknik Siber Cerdika Internasional, 2025)
This research aims to examine the use of Big Data in improving guest experience in international hotels. In the highly competitive hospitality industry, service personalization has become one of the main factors in maintaining guest satisfaction and increasing customer loyalty. Through a qualitative approach with a case study method, this research involves interviews with hotel managers, questionnaires for licensed employees, and direct observation in several international hotels that have adopted Big Data technology. The results show that the use of Big Data enables hotels to provide more personalized services, such as offering relevant recommendations based on guest preferences, as well as improving operational efficiency. However, the main challenges found are infrastructure limitations and lack of analytics skills among staff. Hotel employees tend to accept the use of Big Data in improving services, despite concerns regarding privacy and management of guests' personal data. This research concludes that while Big Data provides great potential to improve guest experience, its successful implementation is highly dependent on investment in staff training and proper infrastructure management. The practical implications of this study suggest that hotels should focus more on service personalization and more effective data management to improve guest satisfaction. This research also opens up opportunities for further studies on the challenges of implementing Big Data in hotels with limited resources.